EBNA-1 gene sequences in Brazilian and American patients with Hodgkin's disease - Chang, K. L.; Chen, Y. Y.; Chen, W. G.; Hayashi, K.; Bacchi, C.; Bacchi, M.; Weiss, L. M. (Amer Soc Hematology, 1999)
We examined the types of Epstein-Barr virus-associated nuclear antigen-1 (EBNA-1) gene carboxy (C)-terminal mutations occurring in Hodgkin's disease (HD) and reactive tissues from two different geographic regions. Previously reported EBNA-1 C-terminal region amino acid sequence variants, based on the amino acid at codon 487, include Prototype (P)-ala, which is found in the B95.8-derived prototype virus, P-thr, Variant (V)-leu, V-val, and V-pro. Using polymerase chain reaction (PCR) to amplify portions of the EBNA-1 gene, followed by DNA sequencing, we found a single EBNA-1 gene sequence variant in each tissue, whether reactive or neoplastic and whether from Brazil or the United States. Variant EBNA-1 gene sequences were more common in both neoplastic and non-neoplastic tissues from different geographic areas than the so-called prototype sequence. In the 17 Brazilian HD cases, 4 cases had P-thr variants and 13 had V-leu variants. In the six reactive tissues from Brazil, one had a P-ala variant, two had P-thr variants, and three had V-leu variants. In the 12 American HD cases, 2 had P-ala variants, 6 had P-thr variants, and 4 had V-leu variants. The 11 American reactive tissues included 2 P ala variants, 5 P-thr variants, and 4 V-leu variants. In both countries, there were similar variant EBNA-1 sequences present in normal tissues and HD cases. Compared with the P ala and P-thr cases, the V-leu cases were more likely to have the 30-bp latent membrane protein 1 (LMP1) gene deletion (P = 0.0075). In addition, cases of HD with the V-leu were statistically associated with a substitution of asparagine for glutamine at codon 322 of the C-terminal portion of the LMP1 gene. Our results suggest that any variation in EBNA-1 gene sequence is caused by a polymorphism present in pre-existing viral strains in the underlying population, and not a mutation occurring during oncogenesis. (C) 1999 by the American Society of Hematology.